Autoantibodies to Factor XII and Kininogen‐Dependent Antiphosphatidylethanolamine Antibodies in Patients with Recurrent Pregnancy Loss Augment Platelet Aggregation. (26th May 2015) - Sato, Yoshihiro; Sugi, Toshitaka; Sakai, Rie
<x xml:space="preserve">Abstract</x> Problem Numerous studies have suggested that factor XII (FXII) deficiency, autoantibodies to FXII (anti‐FXII), and antiphosphatidylethanolamine antibodies (aPE) are associated with recurrent pregnancy loss (RPL). aPE in RPL patients recognize the LDC27 peptide of kininogen domain 3. Anti‐FXII in RPL patients recognizes the heavy chain of FXII, especially the amino‐terminal sequences IPP30 peptide. Previous studies suggested that LDC27 and IPP30 are the responsible sites competing for the same binding site on platelets and inhibiting augmentation of thrombin‐induced platelet aggregation. Our aim was to study the influence of antibodies to LDC27 and IPP30 on platelet aggregation. Methods of study In fifteen healthy volunteers, platelet aggregation induced by γ‐thrombin in the presence or absence of antibodies to LDC27 and IPP30 was measured. Sixteen RPL patients who were positive for anti‐FXII were measured for spontaneous small platelet aggregate (SSPA) formation. Results and Conclusions Antibodies to LDC27 and IPP30 markedly increased aggregation of normal platelets stimulated by γ‐thrombin. Augmentation of SSPA formation was more frequent in the patients with RPL who were positive for anti‐FXII than in the control group (P = 0.003). This study strongly supports the hypothesis that aPE and anti‐FXII may cause RPL due to disruption of the normal antithrombotic effects of kininogens and FXII.